Re-definition and review of the Oriental genus Hexachaetus Chaudoir, 1871 (Coleoptera: Carabidae: Orthogoniini) - Tian, Mingyi; Deuve, Thierry (Zootaxa, 2016)
The ground beetle genus Hexachaetus Chaudoir, 1871 is re-defined and reviewed. Bearing six setae on ligula is no more considered as a crucial characteristic for Hexachaetus. Members of Hexachaetus share the following combination of morphological features: body polish, smooth, and impunctate, ligula more or less dilated at apex, bearing 4, 6, or even 12 setae apically, prosternal process unbordered at apex, elytra distinctly and obliquely truncated at apex, with the apical inner angles very sharp in most species (except for H. mulan n. sp.), and interval 3 with anterior and posterior setiferous pores (median one lacking). The members of Hexachaetus are about 20 species which could be divided into six species groups. All except angulatus species group are dealt with in this paper, with descriptions of four new species: H. kirschenhoferi n. sp. (Indonesia: Kalimantan), H. brunki n. sp. (Malaysia: N. Borneo), H. vietnamensis n. sp. (Vietnam: Annam) and H. mulan n. sp. (Malaysia: Perak and Pahang). H. maindroni Tian & Deuve, 2006 is proposed as a subspecies of H. lateralis Guérin, 1843, n. stat. A key to species groups and species of the genus is also provided.